2016
DOI: 10.1111/hepr.12632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor recurrence after superselective conventional transcatheter arterial chemoembolization for hepatocellular carcinoma: Comparison of computed tomography and gadoxetate disodium‐enhanced magnetic resonance imaging

Abstract: The detectability of tumor recurrence after superselective cTACE with gadoxetate disodium-enhanced MRI was superior to that of CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Artifacts from dense ethiodized oil accumulation deteriorate the image quality of computed tomography (CT), whereas ethiodized oil does not influence the quality of magnetic resonance imaging (26).…”
Section: Embolic Agents Used In Conventional Transarterial Chemoembolmentioning
confidence: 99%
“…Artifacts from dense ethiodized oil accumulation deteriorate the image quality of computed tomography (CT), whereas ethiodized oil does not influence the quality of magnetic resonance imaging (26).…”
Section: Embolic Agents Used In Conventional Transarterial Chemoembolmentioning
confidence: 99%
“…Finally, for the detection of recurrent HCC, contrast-enhanced MRI and diffusion-weighted MRI may also be used, and these modalities have demonstrated promising results (21,22). Previous studies have demonstrated superiority of MRI over MDCT in detecting tumor recurrence after TACE (23,24), but how these techniques compare to the imaging method used in this study is not known. Further studies including both modalities are needed to clarify these issues.…”
Section: Discussionmentioning
confidence: 97%
“…As an alternative, MRI can be used to diagnose an early residual tumor after cTACE with a superior performance in comparison to CT [14]. However, MRI has limitations, since it cannot assess iodine depositions as a marker for the risk of death and progression-free survival [9].…”
Section: Discussionmentioning
confidence: 99%